Effectiveness of Monetary Policy Transmission Path on Usecashless Paymentt and Amount of Money Supply on the Increasing Inflation Rate in Indonesia - Maharani, Era; Sari, Wahyu Indah (Formosa Journal of Sustainable Research, 2024)
The use of cashless payments and the money supply can influence inflation and monetary policy. Modernization of payment instruments carried out by monetary policy in the financial system can control the inflation rate. The aim of this research is to determine the effect of cashless payments and money supply on inflation with other variables such as e- money, debit cards and interest rates. Using the vector autoregression (VAR) analysis method, it is found that e-money has an effect on the amount of money in circulation and debit cards. Then inflation is also influenced by debit cards, e-money and the amount of money in circulation